Program Pengembangan Pegawai untuk Menciptakan Sumber Daya Manusia yang Kompetitif - Dr. Ahmad Azmy, SE, MM (Journal of Management and Leadership, 2018)
Employee development program is a long-term investment by the company to increase capacity and capability. The methods employed in employee development include job rotation, empowerment, technical training, and work delegation. Results of research studies conducted that the development of employees able to improve performance both individually and organization. Employee development has a long-term view of the future and creates human resources according to company expectations. Therefore, the development of employees must be done to anticipate business changes very quickly.